PENGARUH LITERASI KEUANGAN DAN RETURN TERHADAP MINAT BERINVESTASI DI GALERI INVESTASI SYARIAH FEBI UIN STS JAMBI - Rati lestari; Putri apria ningsih; Kurniyati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
In the word of investment investors’ interest in investing is influenced by financial literacy factors, apart from that, the return is the consideration for investing. This research aims to determine the influence of financial literacy and returns on interest in investing in the FEBI UIN STS Jambi sharia investment gallery. This research uses a quantitative approach with multiple linear regression data analysis methods. The research results show that financial literacy has a significant effect on investment interest, so it can be concluded that Ha is accepted and Ho is rejected. Return shows a significant effect on investment interest, so it can be concluded that Ha is accepted and Ho is rejected. Meanwhile, financial literacy and return simultaneously have a significant effect on investment interest. The influence of these two variables is 42.8%, while the remaining 57.2% is influenced by other variables outside the variables in this study.